(untitled) (Numerus academy review, 2026)
This paper addresses the guarantees established by the Algerian legislature in the Code of Criminal Procedure for the non-abuse of the right to television eavesdropping, interception of telecommunications in the context of investigation, investigation of serious crimes, seizure of criminal evidence and its effectiveness in balancing the individual’s interest in the violation of privacy and the interests of society In protecting him from crime.